The Interpretation of Subjective Value Theory in the Writings of the Austrian Economists - Sweezy, A. R. (Review of Economic Studies, 1934)
Journal Article The Interpretation of Subjective Value Theory in the Writings of the Austrian Economists Get access Alan R. Sweezy Alan R. Sweezy Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 3, June 1934, Pages 176–185, https://doi.org/10.2307/2967481 Published: 01 June 1934